Role of gabapentin enacarbil XR in restless legs syndrome - Yee BJ; Sivam S (Therapeutics and Clinical Risk Management, 2012)
Sheila Sivam1,2, Brendon J Yee1,21NHMRC Centre for Sleep Health, Woolcock Institute of Medical Research, University of Sydney, Sydney, 2Department of Respiratory and Sleep Medicine, Royal Prince Alfred Hospital, Camperdown, New South Wales, AustraliaAbstract: Gabapentin enacarbil XR is a new extended-release formulation which attempts to overcome the reduced efficacy of shorter-acting gabapentin, with sustained delivery over a 24-hour period. It is a gabapentin prodrug which is efficiently and rapidly converted to gabapentin during active transport throughout the length of the intestine via high-capacity monocarboxylate type 1 nutrient transporters unlike its predecessor, which is absorbed via low-capacity transporters largely confined to the upper intestinal region. Its lack of saturable absorption allows for dose-proportional absorption and hence increased bioavailability. Several clinical trials addressing its efficacy in moderate to severe restless legs syndrome (RLS) demonstrate improvements in the International RLS Rating Scale after a 2-week to 3-month period. Open-label studies of 52 weeks’ duration showed maintenance of symptom reduction with once-daily administration of the extended-release formulation. The most commonly reported treatment-emergent adverse effects were somnolence and dizziness. Although the incidence of emergent adverse effects is high, it is comparable with that of gabapentin. No studies thus far have documented augmentation as an issue, unlike that observed with most dopaminergic agents. In addition, both dopamine precursors and agonists have not been shown to increase slow wave sleep or improve overall sleep architecture consistently despite improvement in the periodic leg movement index, in contrast with gabapentin enacarbil. Presently, gabapentin enacarbil has not been approved by the Therapeutic Goods Administration or Medsafe for use in RLS. The cost of this medication may also be a potential barrier for many patients. Future comparative efficacy studies with gabapentin, first-line dopaminergic agents, rotigotine, being the other once daily RLS medication, and pregabalin, the structural analog of gabapentin, will be necessary.Keywords: extended-release gabapentin, restless legs syndrome